2005
DOI: 10.2337/diabetes.54.6.1816
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Excretion Rate and Cardiovascular Risk

Abstract: Elevated albumin excretion rate (AER) independently predicts total and cardiovascular mortality in a variety of conditions, although the exact mechanisms are unknown. Laser Doppler fluximetry was used to study associations with risk factors and renal damage (AER calculated from a timed overnight urine collection) in 188 people without diabetes and 117 individuals with diabetes. Skin flow (flux) in response to arterial occlusion (ischemia) was measured. Three distinct patterns of postischemic peak flow were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 32 publications
6
50
0
Order By: Relevance
“…[33][34][35][36] Our results are consistent with prior investigations reporting an impaired myogenic vasoconstriction in the microcirculation of diabetic patients undergoing PORH measured by laser Doppler fluxmetry. 21,22 Both a thickened arterial wall structure and endothelial dysfunction have been made responsible for this decline in microvascular functionality. Furthermore, microvascular dysfunction, as described in obese adults, was attributed to various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Our results are consistent with prior investigations reporting an impaired myogenic vasoconstriction in the microcirculation of diabetic patients undergoing PORH measured by laser Doppler fluxmetry. 21,22 Both a thickened arterial wall structure and endothelial dysfunction have been made responsible for this decline in microvascular functionality. Furthermore, microvascular dysfunction, as described in obese adults, was attributed to various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Constriction of these precapillary arterioles prevents terminal capillaries from hyperperfusion. 11 As peak perfusion directly reflects microvascular reactivity, peak perfusion was used as primary outcome variable in this study.…”
Section: Porhmentioning
confidence: 99%
“…11 PORH as measured by laser Doppler fluxmetry potentially reveals subclinical microangiopathy upon metabolic disorders, such as diabetes. 8,[11][12][13][14] Focusing on GDM, previous research has shown that women with pGDM face an increased risk of macrovascular problems. 15,16 In contrast to GDM-induced macrovascular complications, data on the impact of GDM on microcirculation are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations